Using Videos in Blended E-Learning for a Structural Steel Design Course - Bilal EL-Ariss; Essam Zaneldin; Waleed Ahmed (MDPI AG, 2021)
Conventional methods of teaching structural engineering topics focus on face-to-face delivery of course materials. This study shows that using video-based e-learning in delivering an undergraduate Structural Steel Design course satisfactorily achieved most of the course learning outcomes. Video-based e-learning with animations and simulations gives students a profound understanding of the course intricate design materials. To gauge the effectiveness of video-based e-learning of the course, an online evaluation was conducted by sixty-eight undergraduate students at the United Arab Emirates University using Blackboard. The evaluation consisted of an online survey that was accessible by students who took the structural steel design course in the academic year 2019 using instructional videos provided to them as Quick Response (QR)-codes. The structural steel design course has six learning outcomes (CLOs), and the performance of students in the six CLOs was compared with that of students who took the same course in the academic year 2018 using the traditional face-to-face lecturing method. The survey data was statistically analyzed, and the results revealed that students' performance improved, and most of the CLOs were attained. Video-based e-learning with animations resulted in better learning outcomes compared to face-to-face lecturing. Accessing the course instruction videos anytime and anywhere is one of the remarkable benefits to the students studying through the e-learning approach.